Structural Investigation of Service Quality in Conventional and Islamic Banking in Pakistan - Muhammad Imran Qureshi; Aamir Khan; Khalid Zaman (International Review of Management and Marketing, 2012)
The objective of the study is to examine the determinants of expected service quality in conventional and Islamic banking in Pakistan. A convenient sample of eight hundred customers from eighty branches of five conventional and five Islamic Banks in Khyber Pakhtoonkhawa (KPK) province of Pakistan participated in the study. A self designed questionnaire was used for data collection. Total of five hundred and thirteen filled–out questionnaires were returned, of which 38% were filled out by female customers and 62% by male customers, forming a rate of 64% of total distributed questionnaires. The result indicates that there is a significant relationship between expected service quality and three of their determinants i.e., bank’s tangibles, responsiveness and assurance, while there is a weak relationship has been observed from reliability and empathy over service quality in commercial banks. On the other hand, there is a significant relationship between expected service quality and its determinants i.e., tangibles, reliability, responsiveness, assurance and empathy in case of Islamic banks. The results of the study are of value to both academics and policy makers.